Delayed retention of new word-forms is better in children than adults regardless of language ability: a factorial two-way study - Bishop, D; Barry, J; Hardiman, M (Public Library of Science, 2012)
Background Nonword repetition, the ability to retain and repeat unfamiliar sequences of phonemes is usually impaired in children with specific language impairment (SLI), but it is unclear whether this explains slow language learning. Traditional nonword repetition tests involve a single presentation of nonwords for immediate repetition. Here we considered whether rate of learning of novel phonological sequences was impaired when the same items were presented repeatedly. Methodology/Principal Findings Three complex nonwords were each presented for repetition five times in two sessions (A and B) separated by one hour. We studied both adults and children from (i) families with a child with SLI and (ii) families whose children did not have SLI. This gave a 2×2 design with familial SLI as one factor, and age (up to or above 18 years) as the other. Overall, participants from families with SLI were poorer at nonword repetition than their peers from typical-language families, and there was a trend for children with SLI to show less within-session learning than typically developing children. However, between-session retention, measured as the difference between the last trial from session 1 and the first trial of session 2, showed a significant age effect, η2 = .139, p = .004, regardless of family SLI status. Adult participants showed a decrease in score from the last trial of session A to the first trial of session B, whereas children maintained their level of performance, regardless of whether or not they had SLI. Conclusions/Significance Poor nonword repetition in SLI appears to reflect inadequate encoding of phonological information, rather than problems retaining encoded information. Furthermore, the nonword learning task is consistent with the notion of a sensitive period in language learning: Children show better retention over a delay for new phonological sequences than adults, regardless of overall level of language ability.